KEARIFAN LOKAL DALAM KONTEKS PARIWISATA BERKELANJUTAN: FENOMENA DUA SISI PENERAPAN TRI HITA KARANA DALAM KESEHARIAN KEGIATAN PARIWISATA DI BALI - Sitohang, Lidya; Purnomo, Nugroho Hari (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2023)
The tourism development in Bali has put large environmental pressure on the island. This research critically examines the application of local wisdom values as cultural philosophical tenets in terms of sustainable tourism activities. It employs qualitative rapid appraisal approach and literature reviews in seeking the environmental issues accompanying the tourism activities, critically examining the causes of these problems and to gain better understanding of these problems in relation to Tri Hita Karana in Ubud District, Bali. Results show that the largest environmental problems in the island is waste. The waste is generated from the community activities regarding traditional ceremonies as well as tourist activities. It turns out that the is paradox in the practice of Tri Hita Karana in the context of sustainable tourism. Such concept that seeks to maintain the harmony of man's relationship with God, others and nature has not been able to necessarily overcome the waste problem Keywords: sustainable tourism, local wisdom, Tri Hita Karana